A comparison of six vetches (Vicia spp.) for developmental rate, herbage yield and seed yield in semi‐arid central Turkey. (28th December 2012) - Fırıncıoğlu, Hüseyin Kansur
Abstract Six vetches (Vicia spp.), represented by 96 accessions, were evaluated for herbage yield, seed yield and related characters in three consecutive growing seasons (1995‐98) in semi‐arid central Turkey. Data were analysed by multiple statistical procedures: principal component analysis, restricted maximum‐likelihood method and simple linear regression analysis. In the first growing season (Y1), the growing period was curtailed by summer drought, and in the second (Y2) by heavy rainfall. In the third season (Y3), conditions were more temperate. Vicia pannonica ssp. pannonica (Pan) and V. villosa ssp. villosa (Vil) produced more biomass in Y3 than in Y1 and Y2, while V. pannonica ssp. purpurascens (Pur) and V. villosa ssp. dasycarpa (Das) produced more biomass in the wetter Y2. In the shorter growing seasons (Y1 and Y2), the earliness of Pur and Das resulted in high seed yield. V. narbonensis (Nar) in Y3 was particularly sensitive to widely fluctuating air temperatures with the accompanying high rainfall at the vegetative stage, which resulted in vigorous vegetative growth, hindered flowering and reduced seed yield. In V. sativa ssp. sativa (Sat), biomass and seed yield were significantly increased by the longer period of favourable growing weather during Y3. In agricultural practice, Pan and Vil have great potential for herbage production and grazing; Pur, Nar and Sat for grain and straw production; and Das for both hay and grain crops.